Thermoelectric properties of In-rich InGaN and InN/InGaN superlattices - James (Zi-Jian) Ju; Bo Sun; Georg Haunschild; Bernhard Loitsch; Benedikt Stoib; Martin S. Brandt; Martin Stutzmann; Yee Kan Koh; Gregor Koblmüller (AIP Advances, 2016)
The thermoelectric properties of n-type InGaN alloys with high In-content and InN/InGaN thin film superlattices (SL) grown by molecular beam epitaxy are investigated. Room-temperature measurements of the thermoelectric properties reveal that an increasing Ga-content in ternary InGaN alloys (0 < x(Ga) < 0.2) yields a more than 10-fold reduction in thermal conductivity (κ) without deteriorating electrical conductivity (σ), while the Seebeck coefficient (S) increases slightly due to a widening band gap compared to binary InN. Employing InN/InGaN SLs (x(Ga) = 0.1) with different periods, we demonstrate that confinement effects strongly enhance electron mobility with values as high as ∼820 cm2/V s at an electron density ne of ∼5×1019 cm−3, leading to an exceptionally high σ of ∼5400 (Ωcm)−1. Simultaneously, in very short-period SL structures S becomes decoupled from ne, κ is further reduced below the alloy limit (κ < 9 W/m-K), and the power factor increases to 2.5×10−4 W/m-K2 by more than a factor of 5 as compared to In-rich InGaN alloys. These findings demonstrate that quantum confinement in group-III nitride-based superlattices facilitates improvements of thermoelectric properties over bulk-like ternary nitride alloys.